Aplikasi Pos Pelayanan Terpadu (Posyandu) Berbasis Android Menerapkan Metode Research and Development - Fikran Anwar; Bahtiar Senung; A Mulawati Mas Pratama; Abdul Rahman Ismail (STMIK Budi Darma, 2023)
Buloila Public Health Center is one of the public health centers in the district of Sumalata, North Gorontalo District. Posyandu activities undertaken at the Buloila posyandu have been carried out well. To support a variety of posyandu activities, it is necessary to have a posyandu application that can be used to facilitate the running of posyandu activities. Posyandu participants often forget to carry out Posyandu every month because the information provided by the puskesmas is only in the form of manual information by providing information in several places within the puskesmas. So sometimes the information does not reach the posyandu participants in the area. The purpose of this study is to design an Android-based posyandu service application at the Puskesmas Buloila Buloila Village, Sumalata District, North Gorontalo District. The method used is the Research and Development method. Application made with Java, PHP and HTML programming. Database that is used in MySql Language. For modeling using UML (Unified Modeling Language). For testing this system uses whitebox and blackbox testing where with this test the correct flow chart is obtained as a sample. The researcher conducts a test on the flowchart. , and the value of Cyclometic Complexity (CC) = 3.